Prenatal exposure to bisphenol A and autistic- and ADHD-related symptoms in children aged 2 and5 years from the Odense Child Cohort - Julie Bang Hansen; Niels Bilenberg; Clara Amalie Gade Timmermann; Richard Christian Jensen; Hanne Frederiksen; Anna-Maria Andersson; Henriette Boye Kyhl; Tina Kold Jensen (BMC, 2021)
Abstract Background Bisphenol A (BPA) is a non-persistent chemical with endocrine disrupting abilities used in a variety of consumer products. Fetal exposure to BPA is of concern due to the elevated sensitivity, which particularly relates to the developing brain. Several epidemiological studies have investigated the association between prenatal BPA exposure and neurodevelopment, but the results have been inconclusive. Objective To assess the association between in utero exposure to BPA and Attention Deficit/Hyperactivity Disorder (ADHD-) symptoms and symptoms of Autism Spectrum Disorder (ASD) in 2 and 5-year old Danish children. Method In the prospective Odense Child Cohort, BPA was measured in urine samples collected in gestational week 28 and adjusted for osmolality. ADHD and ASD symptoms were assessed with the use of the ADHD scale and ASD scale, respectively, derived from the Child Behaviour Checklist preschool version (CBCL/1½-5) at ages 2 and 5 years. Negative binomial and multiple logistic regression analyses were performed to investigate the association between maternal BPA exposure (continuous ln-transformed or divided into tertiles) and the relative differences in ADHD and ASD problem scores and the odds (OR) of an ADHD and autism score above the 75th percentile adjusting for maternal educational level, maternal age, pre-pregnancy BMI, parity and child age at evaluation in 658 mother-child pairs at 2 years of age for ASD-score, and 427 mother-child pairs at 5 years of age for ADHD and ASD-score. Results BPA was detected in 85.3% of maternal urine samples even though the exposure level was low (median 1.2 ng/mL). No associations between maternal BPA exposure and ASD at age 2 years or ADHD at age 5 years were found. Trends of elevated Odds Ratios (ORs) were seen among 5 year old children within the 3rd tertile of BPA exposure with an ASD-score above the 75th percentile (OR = 1.80, 95% CI 0.97,3.32), being stronger for girls (OR = 3.17, 95% CI 1.85,9.28). A dose-response relationship was observed between BPA exposure and ASD-score at 5 years of age (p-trend 0.06) in both boys and girls, but only significant in girls (p-trend 0.03). Conclusion Our findings suggest that prenatal BPA exposure even in low concentrations may increase the risk of ASD symptoms which may predict later social abilities. It is therefore important to follow-up these children at older ages, measure their own BPA exposure, and determine if the observed associations persist.